Perfect Optical Vortex to Produce Controllable Spot Array - Jiang, Xiaotong; Tian, Yuyuan; Sun, Meiyu; Li, Zhigang; Zhang, Dengying; Cao, Kunjian; Shi, Qiang; Zhu, Linwei (Frontiers in Physics, 2022)
The perfect optical vortex has successfully aroused substantial interest from researchers for its central dark hollow caused by spatial phase singularity in recent years. However, the traditional methods of combining the axicon and helical phase to generate the perfect optical vortex lead to an additional focus deviation in the tightly focused systems. Here, we report a multi-foci integration (MFI) method to produce the perfect optical vortex by accumulating a finite number of foci in the focal plane, to overcome the additional focus deviation. Furthermore, based on MFI, we superposed two perfect optical vortices to obtain the spots array with controllable phase distribution and the number of spots. This work deepens our knowledge about superposed vortices and facilitates new potential applications. The micro-manipulate experimental results agree well with our theoretical simulation. The spots array field provides new opportunities in direct laser writing, optical tweezers, optical communications, and optical storage.